Relating Nocturnal Enuresis with Self-esteem among Adolescents Patients in Baghdad City - Alwan , Iman Hussaein; Hussein, Hassan A.; Ahmed, Hayder A. (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The study aimed to Identifying the impact of nocturnal enuresis on Adolescents selfesteem. Finding out the relationship between nocturnal enuresis and adolescents demographical characteristics such as: (age, sex, and economic status) in Baghdad City Methodology: A descriptive - analytic study was conducted at(Ibn-Rushid) Psychiatric Teaching hospital. The study was carried out through the period of November 20th 2018 to March 15th 2019 Which consist of 50 participant to assessing the impact of natural enuresis upon adolescent self-esteem both gender (male and female). A questionnaire based on comprehensive review of relevant literature and previous studies. For the purpose of the study, questionnaire format is designed and constructed by the investigator depending on: Developed psychological questions to measure the variables underlying the present study. Extensive review of available literature and studies related to the concept of psychological status for adolescents with (NE). The questionnaire format constructed consists of two aspects which include all items related to the study purpose. Therefore, the study instrument consists of two parts: Adolescents Demographic Data. This section includes data concerning the participants’ demographic characteristics of gender, age, sex and level of economic status. This aspect contains a questionnaire format that comprises structured questions (10 items) concerning the Patients’ Health Knowledge related to EN that that are measured on a 3-point Lakert type scale and rated as 1 = never, 2 = sometimes and 3 = always. This aspect contains a questionnaire format that comprises structured questions (20 items) concerning the patients’ psychological problems in relation to NE that are measured on a 3-point Lakert type scale and rated as 1 = never, 2 = sometimes and 3 = always. Data Collection Methods: The questionnaire has been submitted to each adolescent having EN, after taking the initial consent of each adolescent to participate in the study. The data is collected by the investigator through a questionnaire format and using semi structured interviews, all interviewed carried by meeting with adolescent conducted hospital administration from time to time, the purpose of the study is explained to the adolescent. The data collection process has been performed from February 1st through March 15th 2014. Each adolescent complete the interview and fill the questionnaire format by self-administrative method. The data have been collected through the utilization of the interview. Data were analyzed through the application of descriptive statistical (frequencies and percentages).and inferential analysis chi by applying the Statistical Package for Social Science version 21.0(SPSS) The validity and reliability of the instrument was determined by using through the panel of experts from different specialties related to the field of the present study. They have more than 10 years of experience at their job field to check and review the clarity, relevancy and adequacy of the questions to measure the concept of interest of this study. This panel includes (10) experts and internal consistency use through the computation of Alpha Correlation Coefficient. Result: The finding of the study showed that the highest percentage is located within the age group of12-13 and 14-15 ( 17=34.0 %).the sample was male and represents 37 (74.0%), distribution of participants within Parents’ Living Status was living together 42 84.0%) reveals that more than half of participants have fair information about enuresis (n= 26; 52.0%), followed by less than half who has good information (n= 23; 46.0%). Conclusion: The study concluded that enuresis in this study sample mostly occurs in male more than in female. Most of the study sample are at age group (12-13). Recommendation: Researcher recommended Educational programs should be carried out by the community health nurses in order to increase public health awareness about the nature of enuresis and provide mothers with information related to risk factors of enuresis in natural development of bladder control, methods of prevention and child psychological needs.